Effectiveness of The Role of Suburb Public Paratransit on Passenger Transport - Ras, Syaiful Abbas; Primadi, Andri; Shahreza, Dhona (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2014)
Transportation is a major component given its function as an important supporting system for mobility of society, as a result, the existence of public transport both within the city and the suburb is really necessary. Para transit transportation in many areas in Indonesia including in Jakarta also play an important role in supporting the transportation system as a whole. In fact, in Jakarta there are still many passengers are dependent to this mode of transportation. Therefore, there is a need to conduct a study focusing in how this sub-urban transportation system take its role as a connecting hub from rural areas to the urban areas. Using of qualitative and quantitative methods, data analysis clearly shows how the suburb public paratransit carries passengers (named KWK) in East Jakarta, in this case PGC- Mekarsarui route,is valued important by the community and it has been running well.